High-altitude hypoxia exacerbates gastric mucosal damage and regulates the Nrf2 signaling pathway in Helicobacter pylori-infected mice - Li, Chunxia; Wang, Xuehong; Cui, Sen (Frontiers in Physiology, 2026)
IntroductionHelicobacter pylori (H. pylori) infection is a primary etiological factor in gastric mucosal injury. High-altitude hypoxic environments are suspected to exacerbate this damage, although the precise mechanisms remain poorly defined. This study aimed to investigate the impact of high-altitude hypoxia on the gastric mucosal barrier and the Nrf2 signaling pathway in H. pylori-infected mice.MethodsMale C57BL/6 mice were randomly divided into four groups: the control group (Con), the hypoxia group (H), the H. pylori infection group (Hp), and the combined H. pylori infection with hypoxia group (HpH), with 10 mice per group. A mouse model of H. pylori infection under hypoxic conditions was established by combining a hypobaric chamber simulating an altitude of 5000 m with H. pylori gavage. Pathological changes in the gastric mucosa were observed by HE staining. The expression of tight junction proteins, apoptosis-related proteins, oxidative stress markers, inflammatory factors, and key molecules of the Nrf2 pathway in gastric tissues were evaluated using qRT-PCR, immunohistochemistry, Western blot, and biochemical analysis.ResultsCompared to the H and Hp groups, mice in the HpH group exhibited significantly higher gastric mucosal epithelial damage scores. This group also showed decreased expression of ZO-1, Occludin, and Bcl-2 in gastric tissues, along with increased expression of Bax and Caspase-3. Furthermore, in the HpH group, the gastric levels of MDA, TNF-α, IL-1β, and IL-6 were elevated, while the activities of SOD and GSH-Px were reduced. Additionally, the HpH group displayed increased expression levels of Keap1 in gastric tissues, along with decreased levels of Nrf2 and its downstream target genes HO-1 and NQO1.DiscussionHigh-altitude hypoxia exacerbates oxidative stress and inflammatory responses induced by H. pylori infection, reduces tight junction protein expression, and triggers changes in apoptosis-related protein expression, exacerbating the disruption of the gastric mucosal barrier, consequently leading to more severe gastric mucosal damage. The underlying mechanism may be associated with the inhibition of the Nrf2 signaling pathway in the gastric tissues.